2013
DOI: 10.1109/jphot.2013.2276742
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Preferences to Color Quality of Illumination of Different Artwork Objects Revealed by a Color Rendition Engine

Abstract: The preferences to color quality of illumination were investigated for American and Chinese subjects using a solid-state source of white light with the continuously tunable color saturation ability and correlated color temperature of quadrichromatic blends. Subjects were asked to identify both Bmost natural[ and preferred blends. For very familiar objects, cultural differences did not affect the average of the selected blends. For less familiar objects (various paintings), cultural differences in the average s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…One explanation might again follow arguments such as a color constancy hypothesis (Foster, 2011; Liu et al, 2013; Nascimento and Masuda, 2014; Berns, 2016; Pridmore, 2017). It may be that viewers, especially with the representational paintings in Study 1, know how a person ‘should’ look or what colors they ‘should be,’ and thus are not that impacted by actual lighting-related changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One explanation might again follow arguments such as a color constancy hypothesis (Foster, 2011; Liu et al, 2013; Nascimento and Masuda, 2014; Berns, 2016; Pridmore, 2017). It may be that viewers, especially with the representational paintings in Study 1, know how a person ‘should’ look or what colors they ‘should be,’ and thus are not that impacted by actual lighting-related changes.…”
Section: Discussionmentioning
confidence: 99%
“…Across the above studies there is a quite high variability and inconsistency with even basic aspects such as color temperature (CCT) and illumination. Beginning with CCT, a summary of the reviewed studies shows not only do they not often coincide with the beginning rule of thumb of the typical Kruithof/museum 3000 K range, these have been all over the map, often depending on the individual study: e.g., from 2850 or 2900 (Liu et al, 2013; Zhai et al, 2015) to 5500–5950 (Liu et al, 2013; Nascimento and Masuda, 2014), and notably with several studies reporting both lower and higher CCT preferences in the same analyses depending on different viewers or set-ups. At the same time, more advanced statistical models (Yoshizawa et al, 2013) suggest that CCT especially may have an important impact on subjective assessment of art.…”
Section: Review: Lighting Of Art Key Factors and Past Researchmentioning
confidence: 99%
“…appearance of the artwork appear more similar to that under a higher illuminance. Based on the findings in this study and the Hunt effect, it is likely that the preference for sources that can enhance the saturation of colors, in comparison to a reference illuminant, found in past studies could be due to the illuminance levels (Islam et al 2013;Jost-Boissard et al 2015;Judd 1967;Liu et al 2013;Ohno et al 2015;Sanders 1959;Szabo et al 2014;Teunissen et al 2016;Wei, Houser, Allen, and Beers 2014;Wei, Houser, David, and Krames 2014), because the illuminance levels between 200 and 500 lx employed in these studies were significantly lower than daylight illuminance, which can be as high as 1 × 10 5 lx (DiLaura et al 2011). The evaluations made by the observers in a recent study also suggested that the perceived saturation of 42 color samples under an exterior daylight condition (with a luminance of 13,050 cd/m 2 for a reference white) were generally higher than those under an indoor lighting condition (Ou 2016).…”
Section: Discussionmentioning
confidence: 62%
“…Most psychophysical experiments investigating color preference, including those described above, were conducted under a single illuminance level between 200 and 500 lx (Islam et al 2013;Jost-Boissard et al 2009Lin et al 2014Lin et al , 2015Liu et al 2013;Ohno et al 2015;Rea and Freyssinier 2010;Szabo et al 2014;Teunissen et al 2016;Veitch et al 2014;Houser 2016, 2017;Wei, Houser, Allen, and Beers 2014;Wei, Houser, David, and Krames 2014;. Such a range not only ensured that the illuminance was within the range of photopic vision but also covered most of the recommended illuminance levels for general illumination (DiLaura et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…48,49 Cultural, personal, and geographical reasons can also impact the preferred lighting conditions. 50,51 Therefore, the quest for a universal most preferred CCT may be an elusive effort.…”
Section: Limitationsmentioning
confidence: 99%